The research journal TRANSPORT: peer-reviewing process in 2015 - Prentkovskis, Olegas; Junevičius, Raimundas (Transport, 2015)
"The research journal TRANSPORT: peer-reviewing process in 2015." Transport, 30(4), pp. 451–457